Obstacles of Teaching Philosophy for Secondary School Students in the Kingdom of Saudi Arabia - Alotaibi, Badr; Alzahrani , Emad (Dirasat: Human and Social Sciences, 2022)
This study aims to explore cultural and pedagogical obstacles that abstain philosophy teaching at secondary schools according to the perspectives of the teachers who teach philosophical and critical thinking courses in the Kingdom of Saudi Arabia (KSA). For achieving the study objectives, the researcher followed a descriptive- survey method with a study population of (200) teachers, male and female, who was teaching the skills of philosophical and critical thinking course. The study most important results achieved by the study included; finding a set of cultural and pedagogical obstacles to abstain the teaching of philosophy at secondary schools foregrounding the ambiguity of philosophy concepts among the community individuals, besides the absence of professional preparation for the teachers of such courses in the stage of pre-service in teaching. The study was concluded with a set of recommendations includes; urging local media to introduce positive content in regard to philosophy, urging the seminars of philosophy spread in KSA to introduce periodical lectures and symposia simplifies the concept of philosophy to the community in collaboration with the Ministry of Education, introducing of levels-training-courses in regard to the skills of philosophical and critical thinking to teachers in partnership with the private national institutions, finally the study recommends inaugurating of philosophical departments at Saudi universities to support the movement of philosophy in general and support the movement of philosophy education in KSA.